Evaluation of risk factors for impulse control disorder in Parkinson’s disease in northern China - Ren, Wenhua; Qi, Yumeng; Liu, Yan; Yan, YaYun; Zheng, Xiaoqi; Jin, ShuXian; Chang, Ying (Frontiers in Aging Neuroscience, 2023)
Impulse control disorder (ICD) is a common non-motor symptom of Parkinson's disease (PD) for which risk factors remain controversial. The aim of this study was to describe the prevalence of ICD in northern China and to analyze the risk factors associated with ICD, multiple ICDs, and four subtypes. This study enrolled 285 patients who were diagnosed with PD. Each patient was screened using the Questionnaire for Impulse and Compulsive Control Disorders (QUIP). Independent risk factors were obtained using stepwise regression. Also, build a prediction model. The results showed a prevalence of 11.6% for ICD. Stepwise regression analysis showed that ICD was associated with disease duration, motor symtoms, dyskinesia, depression, REM sleep behavior disorder(RBD) and cognitive decline; multiple ICDs were related to coffee history, motor symtoms, dyskinesia, depression, apathy and RBD. The AUC values of the prediction model on the balanced train set, balanced test set, and the original imbalanced data set were 0.93, 0.88 and 0.66, respectively. The risk factors for PD-ICD are complex. These factors are closely associated with the regional economic and cultural background. Clarifying these factors and developing predictive models can help to delay or even prevent the development of ICD through early screening and intervention.